Development of novel temperature-stable Al2O3–TiO2-based dielectric ceramics featuring superior thermal conductivity for LTCC applications - Shigeno, Koichi; Li, Moyuan; Fujimori, Hirotaka (Journal of the European Ceramic Society, 2021)
A new composition was developed using sintering to improve the dielectric properties of low-temperature co-fired alumina (LTCA) containing CuO–TiO2–Nb2O5–Ag2O. By substituting some alumina with rutile TiO2, the second-phase compound could be changed from AgNbO3 to the rutile phase. Further, low-temperature sintering at temperatures below 960 °C was possible, suppressing Al2TiO5 formation during firing. The dielectric characteristics, particularly the temperature coefficient of the resonant frequency (τf) and Q × f values, were improved without significantly reducing the sinterability and thermal conductivity. The dielectric properties of the developed 88Al2O3–12TiO2-based ceramic were εr: 14.7, τf: +0.8 ppm/K, and Q × f: 13,383 GHz (at ∼10 GHz) at a firing temperature of 940 °C. The thermal conductivity was 18.5 W/mK, which is the highest value for reported temperature-stable low-temperature co-fired ceramics (LTCCs). These results provide one of the key technologies for the practical application of LTCCs with superior thermal conductivities.